2019
DOI: 10.1056/nejmoa1812405
|View full text |Cite
|
Sign up to set email alerts
|

Bag-Mask Ventilation during Tracheal Intubation of Critically Ill Adults

Abstract: BACKGROUND Hypoxemia is the most common complication during tracheal intubation of critically ill adults and may increase the risk of cardiac arrest and death. Whether positive-pressure ventilation with a bag-mask device (bag-mask ventilation) during tracheal intubation of critically ill adults prevents hypoxemia without increasing the risk of aspiration remains controversial. METHODS In a multicenter, randomized trial conducted in seven intensive care units in the United States, we randomly assigned adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(105 citation statements)
references
References 39 publications
(36 reference statements)
2
100
0
3
Order By: Relevance
“…By contrast, in patients with inadequate spontaneous ventilation, preoxygenation should be undertaken using gentle positive pressure ventilation with BVM. In the intensive care unit (ICU) setting, patients receiving ventilation with BVM during the interval between induction and laryngoscopy had higher oxygen saturations and lower rates of severe hypoxemia than those receiving no ventilation …”
Section: Preparationmentioning
confidence: 99%
“…By contrast, in patients with inadequate spontaneous ventilation, preoxygenation should be undertaken using gentle positive pressure ventilation with BVM. In the intensive care unit (ICU) setting, patients receiving ventilation with BVM during the interval between induction and laryngoscopy had higher oxygen saturations and lower rates of severe hypoxemia than those receiving no ventilation …”
Section: Preparationmentioning
confidence: 99%
“…Although a brief period of apnea is safe after proper preoxygenation in most patients, individuals with preexisting pulmonary disorders may develop severe hypoxemia very rapidly, and maintaining ventilatory support and oxygen supply during intubation may thus be beneficial for patients at risk of severe hypoxemia. Casey et al showed that using BVM ventilation in critically ill patients between induction and laryngoscopy resulted in higher oxygen saturation and a lower incidence of severe hypoxemia compared with patients receiving no ventilation [14]. Miguel-Montanes et al reported that highflow nasal cannula (HFNC) oxygenation significantly improved preoxygenation and reduced the prevalence of severe hypoxemia during tracheal intubation compared with BVM [15].…”
Section: Discussionmentioning
confidence: 99%
“…Each year in the United States, approximately 1.5 million patients are estimated to receive endotracheal intubation and the rate of intubation is increasing in the hospital 1 . Hypoxemia, a frequently reported complication of intubation, is considered a predisposing factor for cardiac arrest and death [2][3][4][5] .…”
mentioning
confidence: 99%